The exploratory study of administrative centralization development model: a case study in Kuala Nerus - Zul Izhar Mohd Zulkifli
Kuala Nerus District is the youngest district of eight districts in Terengganu State including Kuala Terengganu, Marang, Dungun, Kemaman, Setiu, Besut and Hulu Terengganu. The district was approved by the Cabinet Meeting on August 27, 2014. Further to the establishment of this new district, the restructuring of administrative centralizationat the Kuala Nerus District level was introduced by the Jabatan Perkhidmatan Awam Malaysia (JP A). This study was conducted to study the implementation of this centralized administrative structure that houses six government agencies under the administration of the Kuala Nerus District Office which is Jabatan Kerja Raya Daerah Kuala Nerus, Jabatan Kebajikan Masyarakat Daerah Kuala Nerus, Jabatan Pengairan dan Saliran Daerah Kuala Nerus, Jabatan Hal Ehwal Agama Islam Terengganu Daerah Kuala Nerus, Jabatan Pertanian Daerah Kuala Nerus and Jabatan Perkhidmatan Vertarinar Daerah Kuala Nerus. Therefore, this study seeks to achieve three objectives, first identifying the elements involved with the centralization of state agency functions under the Kuala Nerus District Office. The second objective is to identify the job scope of government agencies under the administration of the Kuala Nerus District Office. The third objective to delevop a model of centralization of state agency functions under the Kuala Nerus District Office. To achieve the three objectives of the study, a Focus Group Discussion consisting of 9 members representing their respective agencies. All three objectives were achieved and, in essence, the implementation of the new administrative center structure for the District of Kuala Nerus was made possible with the full cooperation provided by each agency involved at the district level as well as the support of the agencies at the state level.